A Material Flow Analysis in An Integrated Catfish Farming System in Mekong Delta, Vietnam - Tra Thi Hieu; Tra Van Tung; Nguyen Thi Phuong Thao; Le Quoc Vi; Nguyen Hong Anh Thu; Nguyen Viet Thang; Tran Trung Kien; Le Thanh Hai (International Association of Lowland Technology, 2022)
The purpose of this study is to conduct the material flow accounting (MFA) in the integrated catfish breeding system with purpose to evaluate the pollution reduction and the economic benefits gained from the system. An amount of 21.17% of water is evaporated into the air, 4.73% is accumulated in the compost and biomass of cultivation plants, and the larger part of 74.1% after being treated by using aquatic plant flowing in the water ponds is discharged into receiving canal. The pond bottom sludge after being mixed with other organic components in the system is used as compost for fertilizing the cultivation plants. The organic matters accumulated in cultivation plants and soil are 1.95% and 9.6% respectively, and the remaining amount is accumulated in the compost. A larger scale system is recommended for 9 catfish breeding families in the area. However, the wastewater generated from these 9 households is not totally reused for watering purpose due to the limited cultivation land area at these households, thus another households in the neighboring area need to be included in the system in order to form more effective integrated aquaculture system leading to pollution reduction and sustainable livelihood for the local farmers.